Norman Alexander Memorial - Presbyterian Church (1979)
[00:00:00] Choir is singing [00:01:40] Pastor begins to speak about the life and resurrection of Norman Alexander and the family who survives him [00:03:02] Pastor reads scripture from Saint Paul to the Corinthians [00:03:24] Pastor talks about what gives life meaning [00:05:40] Pastor talks about the legacy and purposes that Alexander lived for [00:07:07] Pastor talks about Alexander's home life [00:07:31] Pastor talks about Alexander's work [00:11:34] Choir begins to sing again [00:12:10] Conclusion of the service and final words of appreciation to the family